Tragedi Intelektualualitas Islam Dalam Perspektif Filsafat Politik-Keagamaan ( Diskusi Kasus Nakbah Ibnu Rusyd dan Pembunuhan Faraq Fouda) - Putra, Ario; Fatturohman, Achmad (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The differences that occur sometimes often lead to violence and even end in murder. Islam as a religion that is rahmatan lil 'alamin highly upholds human values, tolerance, and differences. Therefore, Muslims should understand them as fundamental religious values contained in the Qur'an and Sunnah, in order to form a good and peaceful life order. The method used in this research is descriptive-explorative. This research is a library research (Library Research), while the data collection method in this research is by classifying the data related to the research focus, then analyzing it. The findings in this study are that although Islam is a religion that is rahmatan lil 'alamin, in reality it has not been fully realized because throughout its history of development there are still various tragedies and conflicts in Islam. One of them is intellectual tragedy. This tragedy is not due to religious factors, but from the way Muslims are still unable to understand religion properly so that from this lack of understanding emerges intolerant traits and even these traits sometimes lead to murder. One of the tragedies contained in Islam is the intellectual tragedy of the Nakba Ibn Rushd and the tragedy of the murder of Faraq Fouda.